Uji Biologis Iodium dari Rumput Laut (Eucheuma cottonii L.) dan Pengaruhnya terhadap Kemampuan Belajar Tikus Percobaan - Made Astawan; Tutik Wresdiyati; Komari Komari; Ni Nengah Lasmiati (Universitas Atma Jaya Yogyakarta, 2005)
Intelligent is one of human quality factors that can be influenced by nutrition. Iodine is one of trace element nutrition that necessary for intelligent level. The purpose of this research was to learn the effect of seaweed as iodine source on rats learning ability. The rats were divided into four groups based on the ratio: A (without potassium iodide/KI-seaweed flour (SF) 0%), B (with KI-SF 0%), C (without KI-SF 5%) and D (without KI-SF 10%). The ratio had no significant effect on rats growth, but significant on iodine retention, neuron cell number and rats learning ability. Iodine retention value had a positive correlation with the neuron cell number. The neuron cell number of group A, B, C and D were 72.83, 89.33, 93.92 and 100.83 cells per view area, respectively. The number of neuron cells gave a significant influence on rats learning ability. Total time needed by the rats in food retrieval test for the group A, B, C and D was 57.84, 38.17, 33.39 and 20.55 seconds, respectively. The more neuron cell number, the more learning ability.